The gospel of the son of God: an introduction to Matthew - Bauer, David R. (IVP Academic, an imprint of InterVarsity Press, 2019)
Form and genre -- Approach and method -- Circumstances of composition -- Shape of composition -- Interpretation of Matthew 1:1-4:16 -- Interpretation of Matthew 4:17-16:20 -- Interpretation of Matthew 16:21-28:20 -- Jesus: the Christological titles -- Jesus: additional aspects of Christology -- God -- Salvation history and eschatology -- Discipleship.